Relationship between cardiovascular risk factors and coronary artery disease severity assessed by coronary angiography in Turkish patients - Günay, Şeyda; Dereli, Seçkin; Serdar, Osman Akın; Özkaya, Güven; Çalışkan, Serhat (Journal of Surgery and Medicine, 2020)
Aim: Established coronary risk factors are good predictors of the occurrence of coronary artery disease (CAD), but their correlation with angiographic seriousness of the disease is argumentative and may vary among ethnic groups. In this study, we examined which of these factors are associated with the angiographic seriousness in Turkish patients with attested CAD. Methods: A total of 2433 patients who underwent coronary angiography and were diagnosed with critical lesions in at least one coronary artery were included in the study. Coronary risk factors were determined by retrospectively scanning the patient records and the relationship with the angiographic severity of coronary artery disease was investigated. Results: Most patients (36.4%) were between 60-69 years of age and approximately two thirds of patients (76.8%) were men. Hypertension, diabetes mellitus and hyperlipidemia were common cardiovascular risk factors (CRFs), present in 54.8%, 43.2% and 50.3% of patients, respectively. Multiple logistic regression analysis showed that diabetes mellitus, male sex and age since 6th decade significantly raised the risk of multivessel CAD (Odds ratios: 1.29 (1.08-1.54; P=0.004), 1.35 (1.1-1.66; P=0.004), 3.53 (1.85-6.75; P<0.001), respectively). Hypertension and hyperlipidemia were not correlated with CAD angiographic severity. Conclusion: Diabetes mellitus appeared as the modifiable coronary risk factor forecasting multivessel coronary artery disease in Turkish patients.